MOZAIK JOGJA : Philosophical Aspects in the Jogja Planning Gallery Preleminary Design Proposal - Philipus Agus Sukandar; Septi Dwi Cahyani; Junianto; Raqyan Mas Bimatyugra Jati (ARCHITENSA : Architectural Design Journal, 2025)
The Jogja Planning Gallery is a cultural park designed to serve as a showcase for Yogyakarta's arts and craftspeople. The site is located within the philosophical axis of Jalan Malioboro, and, based on the organizers' guidance, the design was required to consider contextual and sustainable aspects. The cluster of buildings and the surrounding environment are expected to embody the philosophy, history, environment, spatial planning, architectural design, and future of Yogyakarta. This concept is embodied in a design that reflects the ideal dimension formed by the superimposition of historical and harmonious dimensions. The historical dimension refers to the philosophical axis of Yogyakarta and the conservation objects on the site: the former Provincial DPRD building and two ancient banyan trees. The dimension of harmony is developed from an imaginary line connecting the actual center point of the former DPRD building with Mount Merapi. The philosophical axis evokes a spiritual connection with the Creator or the journey toward existence. This pilgrimage is depicted as full of physical struggle, symbolizing the temptations of worldly functions on either side of the axis, including the future Jogja Planning Gallery building. These materialistic temptations must be overcome, even though they can be misleading. The axis of harmony symbolizes human creativity, which always strives to achieve material truth, despite its physical limitations. Jogja Planning Gallery is a superimposition of ideals that represent ambiguity, symbolizing a physical journey that must be undertaken with constant remembrance and vigilance because the main thing in life is to achieve spiritual existence.